Molecular epidemiology of HIV-1 in Hungary: an evolving contact zone of colliding virus subtypes - Zsichla, Levente; Adravecz, Lilla; Müller, Dalma; Lemey, Philippe; Lakatos, Áron; Ari, Eszter; Kusejko, Katharina; Kouyos, Roger; Szlávik, János; Lakatos, Botond; Áy, Éva; Müller, Viktor (Frontiers in Microbiology, 2025)
IntroductionAlthough antiretroviral therapy can suppress the transmission of HIV-1, the pandemic persists and continues to evolve. Monitoring virus transmission patterns and evolving variants is therefore essential for improving prevention strategies. To address this need, we present the first comprehensive molecular epidemiological analysis of the HIV-1 epidemic in Hungary—a country in the contact zone of major HIV-1 subtypes A, B, and F.MethodsWe analyzed partial pol sequences obtained from 1,120 Hungarian patients in the context of routine drug resistance genotyping between 2008 and 2024, along with 2,202 international background sequences selected based on sequence similarity. We performed subtyping, drug resistance testing, maximum likelihood and Bayesian phylogenetic inference, distance-based and phylogenetic clustering, and Bayesian phylogeographic analyses to identify domestic clusters and cross-border transmission.ResultsMost sequences (814/1,120) belonged to subtype B; however, the frequency of non-B subtypes (mainly A, F, and several recombinant forms) has increased steadily since 2014, reaching 41.3% in 2024. Phylogenetic analyses identified 136 domestic clusters and a large transmitted drug resistance clade persisting over two decades. Remarkably, one in six recent diagnoses mapped to a single cluster, and approximately a third of all new diagnoses to the five most active clusters. Individuals in larger clusters were more often young, men who have sex with men (MSM), and had higher CD4+ counts. While the most affected risk group is still MSM, suspected heterosexual cases have increased recently, with a clear separation between sub-epidemics. Incorporation of international sequences revealed 149 mixed clusters, 56 mixed monophyletic pairs, and at least 122 independent introductions, linking the Hungarian epidemic predominantly to other European countries (Germany, UK, Poland, Spain, Italy, and Croatia for subtype B; Russia and Poland for subtype A; Romania for subtype F, Italy for CRF18_cpx), and to more distant sources for CRF01_AE (Thailand, China), CRF02_AG (Spain, Cameroon) and CRF56_cpx (Turkey).DiscussionIn summary, recent HIV infections in Hungary stem mainly from domestic transmission among MSM, with a few highly active transmission clusters underscoring the need for targeted interventions. The epidemic is most strongly linked to Western and Central Europe, with increasing introductions and spread of non-B subtypes from Eastern Europe and beyond.